Enhanced astaxanthin production of Haematococcus pluvialis strains induced salt and high light resistance with gamma irradiation. (March 2023) - Yang, Ha Eun; Yu, Byung Sun; Sim, Sang Jun
Graphical abstract: Highlights: γ-Ray was used to select H. pluvialis mutants with strong environmental tolerance. A selected mutant, M5, produced 101.57 mg L −1 of astaxanthin under salt conditions. M5 showed 6 folds higher ω-3 production than wild type cells under salt conditions. M5 showed 85% improved biomass than wild type cells under high light conditions. M5 showed 84% higher astaxanthin content than wild type under high light conditions. Abstract: This study was conducted to increase the productivity of biomass that contains high astaxanthin content by developing a mutant Haematococcus pluvialis strain with strong environmental tolerance. H. pluvialis has a low cell-growth rate and is vulnerable to stressors such as salinity or light intensity, which may hinder large-scale commercial cultivation. A mutant M5 strain selected through 5000-Gy gamma irradiation showed improved biomass and astaxanthin production under high-salinity and high-light intensity conditions. With enhanced SOD activity and overexpressed astaxanthin biosynthesis genes (lyc, crtR-b, bkt2), M5 demonstrated an increase in biomass and astaxanthin productivity by 86.70 % and 66.15 %, respectively compared to those of untreated cells. Also, the omega-3 content of M5 increased by 149.44 % under 40 mM CaCl2 compared to the untreated cells. Finally, even when subjected to high-intensity light irradiation for the whole life cycle, the biomass and astaxanthin concentration increased by 84.99 % and 241 %, respectively, compared to the wild-type cells.